Extracellular domain structures from calcium-sensing and GABA(B) receptors - Fan, Qing R. (Henry Stewart Talks, 2019)
Crystal structures of human GABA(B) receptor extracellular domain in multiple functional states, Agonist vs. antagonist recognition, Identification of novel heterodimer interface associated with receptor activation, Crystal structures of human CaSR in the inactive and active conformations, Discovery of L-amino acids as orthosteric agonists of CaSR, Identification of Ca2+ and PO43 binding sites in CaSR, Universal activation mechanism of class C GPCRs